EFFECT OF FOLIAR APPLICATION WITH POTASSIUM AND ZINC ON GROWTH, POD YIELD AND SEED PRODUCTION OF OKRA - & Aljumail, A. Alrawi & Aljumail (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
Two field experiments were carried out at the College of Agriculture/ University of Baghdad during spring season 2017 on okra "Petra" to study foliar application of potassium and zinc on growth, green pod yield and seed production of okra. Split plot within RCBD design was used with three replicates for both experiments where potassium factor was used within main plot and zinc in sub-plot. Potassium sprayed with concentrations (0, 2000, 4000, and 6000) mg.l-1 while zinc sprayed with the concentrations (0, 30, and 60) mg.l-1. Results were showed that the potassium spray with concentrations 4000 mg.l-1 and the zinc spray with 30 mg.l -1 was superiored in plant height (114.36 and 111.60 cm.plant-1). Leaf area (271.46 and 267.86 dcm2.plant-1). Total chlorophyll (60.54 and 52.11 mg.100g-1 fresh weight). Fresh pods number (59.22 and 56.82 pod.plant-1). Fresh pod weight (5.59 and 5.15 gram.pod-1). Plant yield (331.84 and 301.39 gram.plant-1), respectively. While the potassium spray with concentration of 6000 mg.l-1 and the zinc spray with 60 mg.l-1 was superiored in seeds germination (92.22 and 90.67 %). Rapidity germination (10.28 and 9.99 day). Specific gravity (98.09 and 97.93 seed.5 gram-1). Oil in seeds (21.82 and 21.70 (%. Carbohydrate in seeds (33.98 and 33.42 %). Protein in seeds (22.01 and 21.70 (%, respectively. It could be recommended to use foliar of 4000 mg.l-1 potassium and 30 mg.l-1 zinc to increase growth and green pod yield and recommended to use foliar of 6000 mg.l-1 potassium and 60 mg.l-1 zinc to improve seed qualities.